2019
DOI: 10.1017/s0022215119001154
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative prediction of cholesteatomas from radiology: retrospective cohort study of 106 cases

Abstract: ObjectivePre-operative imaging is often used to predict the extent of a cholesteatoma and anatomical variation to plan for surgery. This study aimed to measure the predictive accuracy of computed tomography findings.MethodsA retrospective cohort study was conducted of all patients in a district general hospital undergoing mastoid surgery within a consecutive 12-month period, in whom computed tomography had been performed prior to operative intervention. The study measured the key findings of pre-operative comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…14,17 Several studies have correlated radiologic findings with intraoperative findings, resulting in good positive predictive values for the prediction of cholesteatoma and its complications in preoperative CT imaging. 18 Nevertheless, the correlation of radiological findings with intraoperative findings on the extension of the cholesteatoma into various retrotympanic subspaces has been investigated only sparsely in the literature. Walshe et al found the accurate radiologic prediction of disease extension with a sensitivity and specificity of 100% each into the sinus tympani in 75% and facial recess in 65% of the total of 20 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,17 Several studies have correlated radiologic findings with intraoperative findings, resulting in good positive predictive values for the prediction of cholesteatoma and its complications in preoperative CT imaging. 18 Nevertheless, the correlation of radiological findings with intraoperative findings on the extension of the cholesteatoma into various retrotympanic subspaces has been investigated only sparsely in the literature. Walshe et al found the accurate radiologic prediction of disease extension with a sensitivity and specificity of 100% each into the sinus tympani in 75% and facial recess in 65% of the total of 20 patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the typical localization in the tympanic or mastoid cavity, associated bony erosions, and possible complications such as labyrinthine fistula, facial nerve canal dehiscence, or tegmen erosion indicate a cholesteatoma in native HRCT 14,17 . Several studies have correlated radiologic findings with intraoperative findings, resulting in good positive predictive values for the prediction of cholesteatoma and its complications in preoperative CT imaging 18 . Nevertheless, the correlation of radiological findings with intraoperative findings on the extension of the cholesteatoma into various retrotympanic subspaces has been investigated only sparsely in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been reported previously, with intra-operative findings identifying posterior external auditory canal wall erosion, mastoid erosion and residual cells along the facial ridge as reliable predictors of cholesteatoma recurrence, and associated with canal wall down procedures, but they have not been linked with pre-operative CT findings. 11–13,22…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been reported previously, with intra-operative findings identifying posterior external auditory canal wall erosion, mastoid erosion and residual cells along the facial ridge as reliable predictors of cholesteatoma recurrence, and associated with canal wall down procedures, but they have not been linked with pre-operative CT findings. [11][12][13]22 Conclusion Utilising readily available pre-operative CT imaging alongside a detailed assessment of possible cholesteatoma recurrence patterns by a radiologist may improve outcomes of revision surgery. Performing pre-operative CT scans increases the rate of accurate diagnosis of recurrent cholesteatoma, reduces the time required to diagnose recurrent disease, and lowers the average age at diagnosis and corresponding revision surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Offering a cost-effective alternative to magnetic resonance imaging (MRI), CT is instrumental in distinguishing cholesteatoma from CSOM by detecting osseous erosion in the tympanum. Although studies have shown that clinicians are capable of diagnosing COM based on CT alone [11][12][13][14][15][16][17], distinguishing between COM subtypes poses greater challenges to the human eye.…”
Section: Introductionmentioning
confidence: 99%